Evaluation of the relationship between osteoporosis, balance, fall risk, and audiological parameters - Berk, Ejder; Koca, Tuba Tulay; Guzelsoy, Saime Sagiroglu; Nacitarhan, Vedat; Demirel, Adnan (Springer London Ltd, 2019)
The aim of the study is to investigate the factors such as balance and audiology parameters and bone mineral density (BMD), which were thought to be associated with the increased risk of fall in osteoporotic patients. Ninety-nine female patients between the ages of 40 and 75 were included in the study. Noise exposure, tinnitus, and vertigo were investigated. BMD measurement, Berg Balance Scale (BBS), Timed Up and Go (TUG), and stabilometry tests were applied to the patients. Patients were divided into three groups according to BMD measurements. Patients with a T score of - 1 and below were considered normal (control) (group 1), those with a T score of - 1 to - 2.5 were considered osteopenic (group 2), and those with a T score of - 2.5 and above were considered osteoporotic (OP) (group 3). BBS was 42.06 +/- 5.00, 47.74 +/- 5.18, and 51.65 +/- 3.64 in groups1, 2, and 3, respectively. The difference between the groups was statistically significant (p = 0.001). OP patients had higher oscillation values in all measurements compared with the control group. However, the difference was statistically significant especially on mobile platforms (p < 0.05). Mean tones of pure tone thresholds at 500-8000 Hz for ears were significantly different in patients with OP compared with controls (p < 0.05 for 500-2000 Hz, p < 0.01 for 4000-8000 Hz). This study demonstrated that BMD reduction was correlated with balance parameters and audiological measurements. Therefore, it can be concluded that OP may affect the risk of fracture occurrence not only by decreasing BMD but also by increasing the risk of falling.
Keywords: Audiological parameters; Balance; Falling; Osteoporosis